Photoluminescence of GaAs nanowires at an energy larger than the zincblende band-gap: dependence on growth parameters. (27th April 2015) - Martelli, Faustino; Priante, Giacomo; Rubini, Silvia
Abstract: In this work we show the possibility of varying the light emission energy from GaAs nanowires within a range of about 40 meV above the zincblende-GaAs band-gap at room temperature and about 50 meV at 100 K. The variable energy emission has been obtained in Au-induced GaAs nanowires grown by molecular beam epitaxy by controlling growth time and V/III flux ratios. We discuss the quantum confinement contribution to the energy differences shown by the different samples and demonstrate that it is negligible. We discuss the obtained results in terms of the existing literature on the band gap of wurtzite GaAs. Our results, combined with those reported in the literature, point out the difficulties of gaining information about bulk properties by investigating nanowires. The achieved control of GaAs NW luminescence energy is able to explain the large spread of data present in the literature; it also opens the way for better understanding and utilization of the electronic properties of GaAs NWs.